Civilization in the Era of Harun Al-Rashid: The Synergy of Islamic Education and Economics in Building The Golden Age of Islam - Anto Apriyanto (Review of Islamic Economics and Finance (RIEF), 2020)
This article discusses the Islamic civilization's description during the Caliph Harun Al-Rashid of the Abbasid Daula, progressing rapidly. His triumph was inseparable from the Islamic education system's synergy role, and the Islamic economic system was implemented and became a characteristic of that time. Historical records show that the Islamic civilization at that time succeeded in bringing and showing the world that Islam was a superpower that could not be taken lightly by its reign of more than 5 (five) centuries. One of the indicators of the triumph of Islamic civilization is an indicator in the rapidly developing economy, be it agriculture, trade, or industry, due to the rapid development of the world of education and research. At that time, education got much attention from the state. However, education cannot succeed without economic support. Therefore, the state gives primary attention to the people's welfare, especially those related to the education component, namely students, educators, education funding, educational facilities, and educational tools. So it is not an exaggeration if the early period of Abbasid leadership encouraged the birth of The Golden Age of Islam.